Perencanaan Simulasi Optical Transport Network Menggunakan Aplikasi Cisco Packet Tracker 8.2.1 - Panji Anom Respati; Shafa Yuniar Yasmin; Ester Risanis Travelya; Didik Aribowo (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Optical Transfer Network (OTN), one of the network topologies that can be taken is switching. Researchers on this occasion tried to plan a simulation on the Cisco Packet Tracer 8.2.1 application. This study aims to connect 1 router, 2 PCs and 2 laptops with optical fiber using optical Transfer Network (OTN). The method used is qualitative with data collection techniques in the form of literature studies and making a simulation on the Cisco Packet Tracer 8.2.1 application.